Application of network pharmacology, bioinformatics, computational molecular docking, and experimental validation to study the anticancer effects of oleanolic acid in oral squamous carcinoma cells - Yin Ting; Wang Hao; Zou Yaqin (Acta Pharmaceutica)
Oleanolic acid (OA) has demonstrated anticancer effects across various cancers, with some derivatives advancing to clinical trials. Howe ver, its precise mechanisms of action remain unclear, especially in oral squamous cell carcinoma (OSCC). This study employed network pharmacology, bioinformatics, molecular docking, dynamics simulations, and experimental validation to explore OA’s anticancer effects in OSCC and elucidate its mechanism of action. OA’s pharmacokinetic and physicochemical properties were assessed using SwissADME and Molsoft, revealing high oral bioavailability and GI absorption. SwissTargetPrediction and SuperPred identified protein targets, whereas GeneCards provided OSCC-related targets. A Venn diagram showed 34 overlapping targets between OA and OSCC. STRING and Cytoscape were used to construct a protein-protein interaction (PPI) network with 32 nodes and 164 edges, identifying HSP90AA1, STAT3, HSP90AB1, PI3KR1, and NFKB1 as key hub genes. Gene ontology and KEGG enrichment analyses highlighted relevant biological processes, molecular functions, and pathways. Molecular docking and dynamics simulations confirmed the strong binding of OA to hub targets. Experimental validation showed that OA inhibited cell viability and colony formation in a dose-dependent manner, induced apoptosis, and downregulated HSP90AA1, STAT3, and PI3KR1 proteins. In conclusion, this comprehensive study combining network pharmacology, bioinformatics, molecular simulations, and experimental assays provides valuable insights into OA’s anticancer potential and detailed mechanism of action in OSCC.